Process development of water-based polyurethane with acrylate terminal group under water vapor permeability and water repellency for nylon fabric. Issue 5 (March 2021) - Kuo, Chung-Feng Jeffrey; Chen, Jiong-Bo; Yang, Chi-Ping; Dong, Min-Yan
This study synthesized water-based polyurethane with acrylate terminal group (WPUA) using the long carbon chain of stearyl acrylate to synthesize hydrophobic poly-stearyl acrylate (PSA). The proposed process could minimize environmental pollution caused by fluorine-containing monomers. As a water-based polyurethane (WPU) end-capping agent, the hydrophobic PSA and the hydrophilic and water vapor permeable WPU are copolymerized to form a WPUA functional resin with simultaneous water vapor permeability (WVP) and water repellency. Here, 2-mercaptoethanol was used to control the molecular weight of PSA to prepare the acrylate end-capping agent. PSA was then employed in WPU to form WPUA, which is characterized by the moisture permeability of WPU and water repellency of acrylic resin simultaneously. During the WPUA process, dimethylacetamide was used as a neutralizer to replace the traditional toxic chemical control drug triethylamine. This study set up the material and chemical structure to replace the toxic chemical-controlled drugs and organofluoride in the traditional preparation of moisture permeable and water repellent materials. The proposed process was proven to reduce the consumption of organic solvent, achieve WPUA copolymer stability, and provided moisture permeable and water repellent functions. In addition, Fourier transform infrared spectroscopy was used to determine the structure of WPUA, while thermogravimetry analysis and differential scanning calorimetry were performed to establish the thermal properties of WPUA. After the WPUA was padded on nylon fabric, its water drop contact angle was observed through a scanning electron microscope. The results showed that the contact angle of nylon fabric increased significantly, water repellency was reached, and WVP rises by 23.75%.